2002
DOI: 10.1152/ajplung.00319.2001
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A deficiency promotes bronchial hyperreactivity in rats by altering muscarinic M2 receptor function

Abstract: Vitamin A deficiency (VAD) remains an important health problem among children in developing countries. Children living in these areas have a higher mortality from respiratory infections, which likely results in part from suboptimal nutrition, including VAD. Bronchial hyperreactivity can follow viral respiratory infections and may complicate the recovery. To investigate whether VAD promotes bronchial hyperreactivity, we have assessed methacholine-induced bronchoconstriction in VAD and vitamin A-sufficient rats.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…A link between VAD and increased airway responsiveness had been previously reported in adult rats exposed to a prolonged VAD diet after weaning (61). The airway hyperresponsiveness was attributed to the reduced expression and function of muscarinic acetylcholine receptor M 2 (Chrm2) and decreased elastic fibers in the interstitium, but there was no structural defect in the airway SM.…”
Section: Figurementioning
confidence: 79%
“…A link between VAD and increased airway responsiveness had been previously reported in adult rats exposed to a prolonged VAD diet after weaning (61). The airway hyperresponsiveness was attributed to the reduced expression and function of muscarinic acetylcholine receptor M 2 (Chrm2) and decreased elastic fibers in the interstitium, but there was no structural defect in the airway SM.…”
Section: Figurementioning
confidence: 79%
“…Animal studies have shown that vitamin A deficiency promotes airway hyperresponsiveness and alters the mechanical properties of the lung parenchyma. Vitamin A deficiency is also associated with a reduced abundance and function of muscarinic M 2 receptors, which may help explain the diminished ability to limit cholinergic-mediated bronchoconstriction [19]. While supplementation with retinoic acid reverses the vitamin A deficiency-induced airway hyperresponsiveness and the decrease in muscarinic M 2 receptors [20], it does not appear to reverse alterations in parenchymal mechanics and structure resulting from vitamin A deficiency [42].…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that offspring born to mothers who received vitamin A before, during and after pregnancy as part of a randomised trial had better lung function than did those whose mothers received placebo [18]. Animal experiments have identified that vitamin A deficiency is associated with airway hyperresponsiveness [19] and that supplementation with all-trans retinoic acid, an active metabolic intermediate of vitamin A, reverses airway hyperresponsiveness associated with vitamin A deficiency [20]. While multiple observational studies [21][22][23][24][25] have found that vitamin A deficiency is associated with a higher risk of asthma, there are no randomised trials to support a causal relationship.…”
mentioning
confidence: 99%
“…Mechanistically, vitamin A may regulate bronchial hyperreactivity by altering the function and abundance of the muscarinic M(2) receptors in bronchial tissue [203]. Moreover, carotenoids may regulate activation of a variety of transcription factors.…”
Section: Vitamin a And Carotenoidsmentioning
confidence: 99%